2021
DOI: 10.1007/978-3-030-49844-3_5
|View full text |Cite|
|
Sign up to set email alerts
|

Signal Transduction in Immune Cells and Protein Kinases

Abstract: Immune response relies upon several intracellular signaling events. Among the protein kinases involved in these pathways, members of the protein kinase C (PKC) family are prominent molecules because they have the capacity to acutely and reversibly modulate effector protein functions, controlling both spatial distribution and dynamic properties of the signals. Different PKC isoforms are involved in distinct signaling pathways, with selective functions in a cell-specific manner.In innate system, Toll-like recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…However, more importantly, these molecules were demonstrated to have involvement in tumorigenesis. IL-1β can influence the MAPK and NF-κB pathways determining various effects depending on the type of cell expressing the IL-1 receptors [38,39]. Furthermore, it was previously shown that IL-1β stimulation promoted the stemness of HNSCC cells via the Smad/ID1 pathway, while similar research on the effects of this cy-tokine on the tumor microenvironment revealed that IL-1β levels correlate with the stages of malignant transformation in different subtypes of HNSCC [40,41].…”
Section: Discussionmentioning
confidence: 95%
“…However, more importantly, these molecules were demonstrated to have involvement in tumorigenesis. IL-1β can influence the MAPK and NF-κB pathways determining various effects depending on the type of cell expressing the IL-1 receptors [38,39]. Furthermore, it was previously shown that IL-1β stimulation promoted the stemness of HNSCC cells via the Smad/ID1 pathway, while similar research on the effects of this cy-tokine on the tumor microenvironment revealed that IL-1β levels correlate with the stages of malignant transformation in different subtypes of HNSCC [40,41].…”
Section: Discussionmentioning
confidence: 95%
“…The immune response GO term belonging to the biological processes category refers to any immune system process that functions in the calibrated response of an organism to a potential internal or invasive threat ( 69 ). However, there are also other biological processes that are involved in host immune response, like those corresponding to the GO terms intracellular signal transduction and signal transduction, as immune response depends on intracellular signaling events ( 70 ). In our study, the genes involved in signal transduction (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…When immune systems function normally, tumor-infiltrating immune cells can eliminate malignant cells and are associated with prognosis [ 76 ]. GO analysis also revealed immune-related responses, such as cell adhesion, signal transduction, antigen processing and presentation, and the inflammatory response [ 57 , 77 , 78 ]. Additionally, MASA is enriched in the angiogenesis process, which is one of the most essential characteristics of cancer [ 59 ].…”
Section: Discussionmentioning
confidence: 99%